Hubungan Pelaksanaan Program Rujuk Balik (PRB) BPJS Kesehatan Dengan Kepatuhan Minum Obat pada Pasien Hipertensi di Puskesmas Meurebo Kabupaten Aceh Barat - Masriana Masriana; Susy Sriwahyuni; Meutia Paradhiba; Wintah Wintah; Siti Maisyaroh Fitri Siregar (Universitas Pahlawan Tuanku Tambusai, 2026)
Hypertension is a chronic disease that requires long-term treatment; however, medication adherence among patients with hypertension remains a major challenge in achieving optimal blood pressure control and preventing complications. Although the BPJS Kesehatan Back-Referral Program (BRP) has been implemented to ensure continuity of care for patients with chronic diseases, many patients with hypertension remain non-adherent to their prescribed medication. This study aimed to analyze the relationship between the implementation of the BPJS Kesehatan Back-Referral Program (BRP) and medication adherence among patients with hypertension at Meurebo Community Health Center, West Aceh Regency. This study employed a quantitative approach using a cross-sectional design. The study population consisted of 365 hypertensive patients enrolled in the BPJS Kesehatan Back-Referral Program, and a sample of 79 respondents was selected using an accidental sampling technique. Data were collected through structured questionnaire-based interviews and analyzed using the Chi-square test with a 95% confidence level. The results showed that 72.2% of respondents experienced a high level of Back-Referral Program implementation, while 75.9% demonstrated good medication adherence. Bivariate analysis revealed a statistically significant relationship between the Back-Referral Program and medication adherence among patients with hypertension (p = 0.001). Patients with a high level of Back-Referral Program implementation were 18.2 times more likely to adhere to their medication than those with a moderate level of program implementation (OR = 18.200; 95% CI = 5.144–64.395). It can be concluded that the implementation of the BPJS Kesehatan Back-Referral Program was significantly associated with medication adherence among patients with hypertension. Optimizing the implementation of the Back-Referral Program through improved healthcare services, health education, and routine patient monitoring is expected to enhance medication adherence and support sustainable hypertension management.